AN ANALYSIS OF DERIVATIONAL SUFFIXES IN JUSTIN BIEBER’S CHANGES ALBUM - Nadhea Lisa Desmara; Fitri Palupi Kusumawati; Aulia Hanifah Qomar (Universitas Muhammadiyah Metro, 2022)
Derivational suffix is a part of linguistics learn about word whichadded by affixes may change the meaning and the part of speech. This researchdeals with the derivational suffix of song lyrics. The researcher focuses onderivational suffix types and function. The objectives of the research were todescribe types and function about change class changing and class maintaining inderivational suffix in song lyrics. Descriptive qualitative method was used toanalyze the data. The techniques used in collecting the data is documentationThis research applied the theory of Plag (2002) to indentify the types ofderivational suffix. From the analysis, it is found that 36 derivational suffixesdivided into 3 types, 21 nominal suffix (is –er, -tion –al, -al –ment –ion –ion, -ment –ion –ence -tion –er –ity –ity ––ness –ion –ity –ion, -ist –ette, -age), 10 adverbsuffix (-y, –ly, –ly, –ly, –ly, –ly, –ly, –ly, -ly, -ly), 5 adjective suffix (: -ful, -ly, -y, -ual, -able). The suffixes which found in the data have 31 word class changingand 5 class maintaining,the researcher conluded that suffix –ly give manycontributions in the suffix found in lyrics of album.